Strength- based approach for building resilience in school children: The case of Gaza - Jalala, Suhayla Said; Latifoğlu, Gözde; Uzunboylu, Huseyin (Anales de Psicología / Annals of Psychology, 2020)
This paper seeks to develop a “Strength-based proactive approach for building resilience in school children” under political crisis to be used by counsellors within Gaza schools to advance social and emotional learning programmes that enhance students' resilience and wellbeing. A mixed- methodological approach was used to collect and analyse data. The qualitative methods included data collection using literature review, (12) interviews with school principals and psychologists and (12) focus groups with parents, counsellors and teachers. The quantitative method included data collection using (619) students’ self-administered questionnaires. The study population consisted of all students of basic education grades in Gaza city. The study sample was random and consisted of (619) students. Statistical analysis was used to analyse the questionnaire and the content analysis was used to analyse qualitative data. Findings obtained in this study reflected that both qualitative and quantitative methods highlighted similar strength factors that support building resilience among school children in Gaza. They define children’s ability to adapt and succeed despite the difficult conditions surrounding them, child positive thinking, providing care, creating a supportive school environment, incorporating resilience topics in curriculum, engaging children in resiliency workshops, building strong relationships between school and family, joining peer groups, and building good relationship with neighbours and relatives. In conclusion, this study comes as the first effort to develop CSBPA model for counsellors in Gaza city and other cities experiencing similar political instability to apply effective approaches for fostering academic learning, resilience and wellbeing of school children.